Correlation between Body Mass Index, Thyroid Function Test and Neck Ultrasound in Euthyroid and Thyroid Disorder patients: a Centre Based Retrospective Study - Upadhyaya, Tirtha Lal; Parajuly, Shyam Sundar; Magar, Dilasma Gharti; Pangeni, Roshan (Journal of Diabetes and Endocrinology Association of Nepal, 2018)
Background: Thyroid dysfunction is a major health issue among the Nepalese population. It is the prone region for iodine deficiency disease. Altered living status, sub-urbanization and behavioral factors among the people are believed to be thyroid sufferers. The effects of hypothyroidism and hyperthyroidism on body weight have been clinically clearly demonstrated however there are only few literatures published showing the relationship between BMI and thyroid function among the two groups of population (euthyroid and thyroid dysfunction). Objective: This study aims to study the relationship of TSH (thyroid stimulating hormone) and thyroid hormones with BMI and neck ultrasound findings in euthyroid and thyroid dysfunction subjects. Methods: This is a centre based retrospective study carried out in Diabetes, Thyroid and Endocrinology Care Centre (DTECC), Pokhara Nepal. The study used the archives of the laboratory and patient clinical information on the Centre during the years 2016 March to 2017 March. Detailed information regarding patientís age, medical history and previous history of smoking and alcohol consumption data, patients BMI (Body Mass Index) and neck ultrasound findings were obtained. Results: Of the total five hundred and six cases, four hundred and forty cases were females and sixty six cases were male. 59.4 percentages of the cases had increased body mass index and about 48 percentages of the total cases had abnormal thyroid function tests. Of the total, neck ultrasound revealed findings suggestive of Hashimoto Thyroiditis in two hundred and forty four cases. Conclusion: Thyroid dysfunction is associated with some components of metabolic syndrome. The thyroid function disorders in conjunction with the strong influence of various environmental factors can increase body weight and lead to obesity. Increased in BMI has strong influence on thyroid hormone level.